THE ROLE STUDENTS’ LOCUS OF CONTROL TOWARD READING SKILL IN GENERAL ENGLISH COURSE - Wahyu Trimastuti; Nur Azizah; Anggi Agatha; Fassa Sridevi Hasibuan (Jurnal Sosio dan Humaniora (SOMA), 2023)
The main objective of the research is to explain about the role of students’ locus of control toward reading skill in general english course. The descriptive quantitative method was employed in this research. The population of the research was the students of first semester secretary of Polytechnic Pajajaran ICB Bandung. To collect the data, the writer used questionnaire to find out the students’ locus of control and reading test to know whether the final test score of the students have a significant progress or not. The students with high locus of control will be encouraged if the teacher gives a chance to them to involve actively in teaching learning process. Their control, of course, influences their achievement, especially in achieving reading skill. On the other hand, students who have low locus of control believe that they have little control or power to affect personal outcomes. They usually do not have any interest in joining the learning process. It can be seen that students who have high locus of control were encouraged to be actively and motivately in learning process. Based on the reserach finding, it can be conclude that students’ locus of control have role in teaching learning process. Therefore, it is suggested that: (1) it is better to know students’ locus of control to improve student’s reading skill; (2) this result of the study can be used as a beginning step to conduct a further research.